From Fields to Futures: Women Farmers and Sustainable Food Systems - Ali, Sk Asraful; Kaur, Ramanjit; Meena, Dileep; Borate, Rohit Bapurao; Saikia, Nilutpal; Prajapati, Sunil Kumar (Chronicle of Bioresource Management, 2025)
Agriculture plays a vital role in India’s economy and rural women form the most productive work force in the economy of a majority of the nations, including India. Agriculture including various sub-sectors employs 80 per cent of all economically active women; they comprise 33 per cent of the agricultural labour force and 48 per cent of self-employed farmers. Despite their significant contributions, women face discrimination in land ownership, pay, decision-making, and access to resources. This article explores their multifaceted roles, challenges, and initiatives aimed at empowerment. Historical contributions, ongoing barriers, and government efforts, such as self-help groups and gender-sensitive policies, are also discussed. Empowering women in agriculture is essential for sustainable development, food security, and equitable growth as emphasized by the UN’s declaration of 2026 as the “International Year of the Woman Farmer.”